Altered Walking and Muscle Patterns Reduce Hip Contact Forces in Individuals With Symptomatic Cam Femoroacetabular Impingement. Issue 11 (September 2018) - Ng, K.C. Geoffrey; Mantovani, Giulia; Modenese, Luca; Beaulé, Paul E.; Lamontagne, Mario
Background: Cam-type femoroacetabular impingement (FAI) is a causative factor for hip pain and early hip osteoarthritis. Although cam FAI can alter hip joint biomechanics, it is unclear what role muscle forces play and how they affect the hip joint loading. Purpose/Hypothesis: The purpose was to examine the muscle contributions and hip contact forces in individuals with symptomatic cam FAI during level walking. Patients with symptomatic cam FAI would demonstrate different muscle and hip contact forces during gait. Study Design: Controlled laboratory study. Methods: Eighteen patients with symptomatic cam FAI were matched for age and body mass index with 18 control participants. Each participant's walking kinematics and kinetics were recorded throughout a gait cycle (ipsilateral foot-strike to ipsilateral foot-off) by use of a motion capture system and force plates. Muscle and hip contact forces were subsequently computed by use of a musculoskeletal modeling program and static optimization methods. Results: The FAI group walked slower and with shorter steps, demonstrating reduced joint motions and moments during contralateral foot-strike, compared with the control group. The FAI group showed reduced psoas major (median, 1.1 newtons per bodyweight [N/BW]; interquartile range [IQR], 1.0-1.5 N/BW) and iliacus forces (median, 1.2 N/BW; IQR, 1.0-1.6 N/BW), during contralateral foot-strike, compared with the control group (median, 1.6 N/BW; IQR, 1.3-1.6 N/BW, P = .004; and median, 1.5 N/BW; IQR, 1.3-1.6 N/BW, P = .03, respectively), which resulted in lower hip contact forces in the anterior ( P = .026), superior ( P = .02), and medial directions ( P = .038). The 3 vectors produced a resultant peak force at the anterosuperior aspect of the acetabulum for both groups, with the FAI group demonstrating a substantially lower magnitude. Conclusion: FAI participants altered their walking kinematics and kinetics, especially during contralateral foot-strike, as a protective mechanism, which resulted in reduced psoas major and iliacus muscle force and anterosuperior hip contact force estimations. Clinical Relevance: Limited hip mobility not only is attributed to bone-on-bone impingement, caused by cam morphology, but could be attributed to musculature as well. Not only would the psoas major and iliacus be able to protect the hip joint during flexion-extension, athletic conditioning could further strengthen core muscles for improved hip mobility and pelvic balance.